2023
DOI: 10.1145/3571730
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Hallucination in Natural Language Generation

Abstract: Natural Language Generation (NLG) has improved exponentially in recent years thanks to the development of sequence-to-sequence deep learning technologies such as Transformer-based language models. This advancement has led to more fluent and coherent NLG, leading to improved development in downstream tasks such as abstractive summarization, dialogue generation and data-to-text generation. However, it is also apparent that deep learning based generation is prone to hallucinate unintended text, which degrades the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
500
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,011 publications
(512 citation statements)
references
References 129 publications
5
500
0
7
Order By: Relevance
“…Prior work has shown that neural language models suffer from contradictions and inconsistency as well as a tendency to “hallucinate,” or generate factually incorrect information ( 29 ). In the complex domain of Diplomacy , dialogue models exhibit both these problems and other more subtle mistakes, such as deviations from the intents used to control the message or blunders in the strategic content of the message.…”
Section: Methodsmentioning
confidence: 99%
“…Prior work has shown that neural language models suffer from contradictions and inconsistency as well as a tendency to “hallucinate,” or generate factually incorrect information ( 29 ). In the complex domain of Diplomacy , dialogue models exhibit both these problems and other more subtle mistakes, such as deviations from the intents used to control the message or blunders in the strategic content of the message.…”
Section: Methodsmentioning
confidence: 99%
“…Out of all explanations, including incorrect ones, explanations included at least one hallucinated reference or authority in approximately 37% of the time. Research is ongoing on the optimal degree of hallucination and techniques for mitigating unwanted hallucination [38], and we will continue to explore these questions and applications in future work. For text-davinci-003, the average is reported across all runs; for other models, a subset of representative prompts and parameters were included.…”
Section: Assessmentmentioning
confidence: 99%
“…Although these natural language processing techniques have the potential to greatly improve the efficiency and effectiveness of software development, there are concerns regarding their use. One problem with large language models is that they can sometimes "hallucinate" [24]. A recent study found that a state-of-the-art model was more likely to generate code containing a vulnerability if the query asked for code without that vulnerability [25].…”
Section: B Using Artificial Intelligence To Generate Codementioning
confidence: 99%